DESIGNING AUTHENTIC ASSESSMENT FOR WRITING SKILL AT THE TENTH GRADE OF SMAN UNGGUL DHARMASRAYA - Riyadi Saputra; Lidiah Marfuah (STKIP Siliwangi, 2022)
TThe assessment in curriculum 2013 is more emphasized on authentic assessment. Authentic assessment is needed in assessing the students' performance. Since the English teacher has a limited understanding of authentic assessment and has not scored rubric therefore, it is necessary to develop an authentic assessment for writing skill. This research aims at finding out the students' needs and to develop authentic assessments for writing skills. This research was a research and development method (R&D) through ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model. This research only focuses and discusses on the design stage. The design stage consists of designing models and scoring rubrics for writing skill. The results of this research show that there are 4 types of models and scoring rubrics, namely: 1) Essay Question, 2) Short answer and sentence completion task, 3) Fill the blank, and 4) Picture cued task. These models were valid and practice categories to be used in assessing or improving students' writing skills. The models of authentic assessment that have been designed effectively can be applied to assess students' writing process because they are based on practical theories that have been developed.